(untitled) (Islamic Sciences Journal, 2023)
Studying the values and foundations is considered the perspective of human thought، it sakes interests that arose the origin of mountain formation، because it simulates his aspirations towards perfection and possessing. The concept of values is still expanding little by little، which has earned the fore among those perfection، Because of consideration، the instuctional and educational process had the best luck، it glorifies maddened among humanity as. This process represents the cornerstone for the development of human beings from all aspects، preparing as an integrated human beings which is able to achieve the desired renaissance and push it towards a prosperous future، In terms of importance on which the educational system is based، religiously، morally and cognitively .Throughout this simple study whion is entitled (foundations and values of the Scientific and educational renaissance in religious education)، we decided to shed light on the orbit of those values in general and the scope effect of religious education in particular.